Primary lymphoma of the heart. A case report - Sheung‐To Chou; Barry Arkles; Gary D. Gill; N. B. Pinkus; Arthur Parkin; John Hicks (1983)
The necropsy findings of a large cell lymphoma involving only the pericardium and myocardium in a 62-year-old woman are reported. The initial presenting symptoms were heart failure followed by rapidly progressive heart block. The diagnosis of cardiac lymphoma was suggested by gallium and blood pool isotope studies, and was subsequently confirmed by operative myocardial biopsy. The clinical course was abrupt, and the patient died before therapy was instituted. While primary cardiac lymphoma is an extremely rare condition, experience in this case suggests that noninvasive isotope studies, particularly gallium and blood pool, are helpful in the diagnosis of atypical cardiomyopathy.